A new Aurignacian engraving from Abri Blanchard, France: Implications for understanding Aurignacian graphic expression in Western and Central Europe. (20th October 2018) - Bourrillon, R.; White, R.; Tartar, E.; Chiotti, L.; Mensan, R.; Clark, A.; Castel, J.-C.; Cretin, C.; Higham, T.; Morala, A.; Ranlett, S.; Sisk, M.; et al.
Abstract: In the excitement of the widely publicized new finds of Aurignacian art from Chauvet, from the Swabian Jura and from as far afield as Pestera Coliboaia in Romania, it has almost been forgotten that a rich corpus of Aurignacian wall painting, engraving and bas-relief sculpture had been recognized and studied before World War I in the Vézère Valley of SW France. Scientific knowledge of the chronological and cultural context of that early-discovered graphic record has been limited by the crude archaeological methods of that pioneering era, and the loss and dispersal of many of the works discovered. In 2011, we launched new excavations and a re-analysis of one of the key sites for such early discoveries, the collapsed rock shelter of Abri Blanchard. In 2012, we discovered in situ a limestone slab engraved with a complex composition combining an aurochs and dozens of aligned punctuations. This new find, recovered by modern methods and dated by molecular filtration and Hydroxyproline 14C, provides new information on the context and dating of Aurignacian graphic imagery in SW France and its relationship to that of other regions. The support is not a fragment of collapsed shelter ceiling and is situated in the midst of quotidian occupational debris. The image shows significant technical and thematic similarities to Chauvet that are reinforced by our reanalysis of engraved slabs from the older excavations at Blanchard. The aligned punctuations find their counterparts at Chauvet, in the south German sites and on several other objects from Blanchard and surrounding Aurignacian sites. In sum, we argue that dispersing Aurignacian groups show a broad commonality in graphic expression against which a certain number of more regionalized characteristics stand out, a pattern that fits well with social geography models that focus on the material construction of identity at regional, group and individual levels.